The Language Learning Strategies of Low Archievers of English as a Second Language in Malaysia - O. A. Rajak, Rashidah Begam (2004)
The effective use of language learning strategies by second language learners plays an important role in overcoming difficulties in communication for both written and spoken purposes and to enhance their proficiency in the language. Hence, the present study investigated the language learning strategies used by 320 low achieving learners of ESL (English as a Second Language) from both urban and rural schools in the state of Selangor, Malaysia. Data obtained via a Respondent Background questionnaire and interviews indicated the low achievers’ perceived reasons for learning the English language. Most of them indicated that they had the interest in learning the English language. The SILL (Strategy Inventory for Language Learning) questionnaire was used to elicit responses on the use of language learning strategies by low achieving learners of ESL and the differences in terms of strategy use between urban and rural low achievers. The overall results obtained demonstrated that the low achieving learners did use language learning strategies but their use was generally of moderate frequency. There was also evidence that urban learners used memory, cognitive, metacognitive, affective, iii and social language learning strategies more often at moderate levels than rural learners who indicated rather low levels of the activity. Results obtained via interviews with teachers indicated that they were not aware of language learning strategies. They also expressed that the low achieving learners did not show interest in the English language lessons. Strategy training was also conducted in this study to determine the extent of benefit that could be derived by low achievers from such training. Results obtained from this quasi-experimental phase of the study revealed that low achieving learners who participated in the training performed better in both written and spoken aspects of language use in the post-tests than those who were not provided the training. Learners’ perception of the strategy training was also positive and they expressed that they benefited from the training. Hence, the findings of the study underscore the need for strategy training especially for low achieving learners of ESL, which may be included in the school curriculum for TESL.